No-Assistant Technique: Simplified Haptic Externalization For Glued IOL - Priya Narang (Delhi Journal of Ophthalmology)
A modified technique for externalizing the haptics in the Agarwal method of glued intrasderal fixation of a posterior chamber intraocular lens (IOL) is described. This technique eliminates the role of an assistant in holding the haptic during the entire surgical manoeuvre and subsequent complications associated with inappropriate handling of the haptic. The technique was used in 45 cases and was reproducible in all cases with no intraoperative complications. This technique is an attempt to make the process of haptic externalization, considered the most technically demanding part of the surgery, more easy and feasible.